Genome-Wide Characterization and Expression Analysis of CAMTA Gene Family Under Salt Stress in Cucurbita moschata and Cucurbita maxima - Yuan, Jingping; Shen, Changwei; Chen, Bihua; Shen, Aimin; Li, Xinzheng (Frontiers in Genetics, 2021)
Cucurbita Linn. vegetables have a long history of cultivation and have been cultivated all over the world. With the increasing area of saline–alkali soil, Cucurbita Linn. is affected by salt stress, and calmodulin-binding transcription activator (CAMTA) is known for its important biological functions. Although the CAMTA gene family has been identified in several species, there is no comprehensive analysis on Cucurbita species. In this study, we analyzed the genome of Cucurbita maxima and Cucurbita moschata. Five C. moschata calmodulin-binding transcription activators (CmoCAMTAs) and six C. maxima calmodulin-binding transcription activators (CmaCAMTAs) were identified, and they were divided into three subfamilies (Subfamilies I, II, and III) based on the sequence identity of amino acids. CAMTAs from the same subfamily usually have similar exon–intron distribution and conserved domains (CG-1, TIG, IQ, and Ank_2). Chromosome localization analysis showed that CmoCAMTAs and CmaCAMTAs were unevenly distributed across four and five out of 21 chromosomes, respectively. There were a total of three duplicate gene pairs, and all of which had experienced segmental duplication events. The transcriptional profiles of CmoCAMTAs and CmaCAMTAs in roots, stems, leaves, and fruits showed that these CAMTAs have tissue specificity. Cis-acting elements analysis showed that most of CmoCAMTAs and CmaCAMTAs responded to salt stress. By analyzing the transcriptional profiles of CmoCAMTAs and CmaCAMTAs under salt stress, it was shown that both C. moschata and C. maxima shared similarities against salt tolerance and that it is likely to contribute to the development of these species. Finally, quantitative real-time polymerase chain reaction (qRT-PCR) further demonstrated the key role of CmoCAMTAs and CmaCAMTAs under salt stress. This study provided a theoretical basis for studying the function and mechanism of CAMTAs in Cucurbita Linn.